PENGARUH PENGGUNAAN AIR KELAPA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG DAUN (Allium fistulosum L.) VARIETAS BLAZE F1 - Wahyu Riyadi (Institute of Computer Science (IOCS), 2023)
In order to examine the effect of coconut water (Cocos nucifera) on the growth and yield of the spring onion (Allium fistulosum L.) Blaze F1 variety, this research was conducted in Plumpung village, Plaosan district, Magetan regency, East Java province, from April to June 2023. Randomized Groups Factorial Design with a single factor used as a method by watering coconut water with six levels, i.e.: P0 (control), P1 (150 ml), P2 (200 ml), P3 (250 ml), P4 (300 ml), and P5 (350 ml). Parameters observed were plant height, number of leaves, number of tillers, leaf diameter, and plant weight. Analysis of Variance (ANOVA = 5%) and the Least Significant Different (LSD) test at the 5% level were used to examine observational data. The results indicated that watering with coconut water had a substantial effect on the growth and yield of the spring onion (Allium fistulosum L.) Blaze F1 variety. Procedure P5 (watering with 350 ml of coconut water) provided the most significant results in terms of plant height, number of leaves, number of tillers, leaves’ diameter, and plant weight. It confirms that coconut water can boost the growth and yield of spring onion (Allium fistulosum L.).